(untitled) (Eurasian Journal of Religious Studies, 2023)
Paul Tillich considers the language of religion with a symbolic language approach. The basis of this understanding make up of Tillich’s God view, his religion understanding and approach to symbol. Because, the symbol is the bearer of truth for Tillich. God is not the God of classical theism, but the focus of human’s ultimate concern as a being in himself. The discussions as to religion have lasted in every period of history. At first, the discussions at the point of the nature of religion evolved on the logical status of religious propositions in the modern period. This situation bring about the need to reconsider religious proposals with today’s experience. God for Tillich is “God beyond God.” Everything to say about this God have been a necessity to be symbolic. According to Tillich, symbols combine finite and infinite. Tillich who maintain that every religion carries the claim of truth and the language that carries these truths should be symbolic, he has been maintained that religion should be symbolic. This article analyzes Paul Tillich’s approach to religious symbols and myths, and also examines the role of symbols and myths in religion.